Comparison of the English translation of the short story Gerhana Mata using ChatGPT and Google Translate: A digital hermeneutics approach - Agustiana, Erika; Hidayat, Nandang; Widya, Widya (Universitas Mulawarman, 2025)
Literary translation presents a unique challenge as it involves not only transferring meaning but also preserving the style, nuances, and cultural context of the original text. While automated translation technologies, such as Google Translate and ChatGPT, are increasingly used, questions remain about their ability to maintain meaning, aesthetics, and cultural integrity in literary texts. This study compares the English translations of the short story Gerhana Mata produced by both tools, analyzing their strengths and weaknesses. A digital hermeneutics approach is used to explore how meaning and cultural context are conveyed in these translations. The research employs a qualitative, comparative design to assess the accuracy of meaning, fluency, and the ability of both tools to preserve literary style and nuances. The results highlight the importance of translation techniques such as transposition, modulation, and adaptation in maintaining grammatical accuracy and cultural relevance. In this study, ChatGPT demonstrates superior performance compared to Google Translate in preserving the original text’s meaning and aesthetic quality. This research contributes to the field of automatic translation, offering insights into how AI tools can be improved for literary translation and cultural preservation.